Parki in njihovi uporabniki - Goličnik, Barbara (Urbani izziv, 2008)
This paper is concerned with urban parks and their use(r)s. It focuses on usage-spatial relationships from two different angles. Firstly, it discusses the actual uses mapped in places, using repeated observation on different days, times and weather conditions. Secondly, it addresses designers' views and beliefs about usage and design of urban parks. However, the paper shows that designers' beliefs and awareness about uses in places, in some aspects, differ from actual use. It stresses the use of empirical knowledge about usage-spatial relationships, which can be gained by using observation and behavioural mapping, in decision-making processes for parks design.
Keywords: javni prostor; mesta; parki; prostorsko urejanje; urbani prostor; zelene površine